Research on the influence of the specific density of the raw material fermented in a biogas reactor on heat distribution - Spodoba М. О.; Spodoba О. О. (Energy and Automation, 2025)
Biogas technologies are becoming increasingly widespread in industrial and domestic facilities. However, the profitability of biogas production depends on the energy consumption to support the fermentation process, so it is necessary to conduct research aimed at reducing energy costs for heating and mixing the raw material being fermented. Raw materials with different physicochemical compositions are used for fermentation, which significantly affects energy costs. The aim of the work is to study the influence of the specific density of the raw material being fermented in a biogas reactor on the energy costs for mixing and changing the Reynolds criterion. The paper presents the constructed mathematical model and research results. The research considered a wide range of changes in the specific density of the substrate from 750 to 1500 kg/m3. According to the research results, graphical dependences of the change in the Reynolds criterion, heat transfer coefficient and heat transfer coefficient were obtained, depending on the change in the specific density of the raw material and the frequency of rotation of the working body of the mixing device. It has been established that the change in the criterion and coefficients depending on the change in the density of the raw material occurs according to a linear law. The results obtained will allow setting a rational rotation frequency of the mixing device in which the heating device is located from the point of view of energy consumption for the processes of mixing and electrical heating of the raw material. Key words: Reynolds criterion, heat transfer coefficient, heat transfer coefficient, specific density of raw materials, anaerobic digestion, mixing